The Role of Teachers in Shaping the Religious Character of Early Childhood - S. Suryani; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the role of teachers in shaping the religious character of early childhood students at TK Muslimat NU Tahunan Tegalombo. The background of this research is the importance of religious character education from an early age as a foundation for children's moral development, especially in the era of digital media advancement that influences children's behavior. This study employs a descriptive qualitative approach with a case study design, involving teachers, the school principal, and parents as informants. Data were collected through interviews, observations, and documentation, and then analyzed descriptively. The results indicate that teachers play their roles through value-based religious learning, exemplary behavior, habituation of daily prayers and worship, and consistent interaction with children. This study reveals that the role of teachers is crucial in instilling religious character, discipline, and social awareness in early childhood, thereby forming a strong moral foundation for their future lives.